The immunogenetics of Behçet’s disease: A comprehensive review - Takeuchi, Masaki (J Autoimmun, 2015)
Behçet’s disease is a chronic multisystem inflammatory disorder characterized mainly by recurrent oral ulcers, ocular involvement, genital ulcers, and skin lesions, presenting with remissions and exacerbations. It is thought that both environmental and genetic factors contribute to its onset and development. Although the etiology of Behçet’s disease remains unclear, recent immunogenetic findings are providing clues to its pathogenesis. In addition to the positive association of HLA-B*51, which was identified more than four decades ago, and which has since been confirmed in multiple populations, recent studies report additional independent associations in the major histocompatibility complex class I region. HLA-B*15, -B*27, -B*57, and -A*26 are independent risk factors for Behçet’s disease, while HLA-B*49 and – A*03 are independent class I alleles that are protective for Behçet’s disease. Genome-wide association studies have identified associations with genome-wide significance (P < 5 × 10(−8)) in the IL23R–IL12RB2, IL10, STAT4, CCR1-CCR3, KLRC4, ERAP1, TNFAIP3, and FUT2 loci. In addition, targeted next-generation sequencing has revealed the involvement of rare nonsynonymous variants of IL23R, TLR4, NOD2, and MEFV in Behçet’s disease pathogenesis. Significant differences in gene function or mRNA expression associated with the risk alleles of the disease susceptibility loci suggest which genes in a disease-associated locus influence disease pathogenesis. These genes encompass both innate and adaptive immunity and confirm the importance of the predominant polarization towards helper T cell (Th) 1 versus Th2 cells, and the involvement of Th17 cells. In addition, epistasis observed between HLA-B*51 and the risk coding haplotype of the endoplasmic reticulum-associated protease, ERAP1, provides a clue that an HLA class I-peptide presentation-based mechanism contributes to this complex disease.